OPTIMIZING ROAD FREIGHT LOGISTICS IN UZBEKISTAN THROUGH REAL-TIME TRACKING AND DIGITAL VISIBILITY PLATFORMS - Muradullaev, Muzammilkhon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
Road freight logistics is becoming increasingly important for Uzbekistan as the country expands trade, strengthens transport corridors, and seeks to improve delivery speed and supply chain transparency. Real-time tracking and digital visibility platforms offer a practical solution for optimizing logistics processes by enabling continuous truck monitoring, route control, estimated time of arrival prediction, and faster communication between drivers, dispatchers, and cargo owners. This article examines the role of such platforms in improving operational efficiency, reducing delays, and supporting better decision-making in road freight management. It also outlines key implementation challenges, including data accuracy, internet connectivity, and user adoption. The article concludes that digital visibility platforms can significantly improve logistics performance in Uzbekistan when combined with reliable operational practices and effective digital integration.